2015
DOI: 10.3109/1061186x.2015.1065833
|View full text |Cite
|
Sign up to set email alerts
|

Systemic delivery of blood–brain barrier-targeted polymeric nanoparticles enhances delivery to brain tissue

Abstract: Delivery of therapeutic agents to the central nervous system is a significant challenge, hindering progress in the treatment of diseases such as glioblastoma. Due to the presence of the blood-brain barrier (BBB), therapeutic agents do not readily transverse the brain endothelium to enter the parenchyma. Previous reports suggest that surface modification of polymer nanoparticles can improve their ability to cross the BBB, but it is unclear whether the observed enhancements in transport are large enough to enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(41 citation statements)
references
References 65 publications
1
40
0
Order By: Relevance
“…It was found that despite being similar in size, drug release profile and in vitro cytotoxicity, the PLA-HBPG NPs showed significantly longer blood circulation and significantly less liver accumulation than PLA-PEG copolymers (Figure 12). Similarly, copolymers consisting of a PLA core and a HBPG shell modified with adenosine, were used to form nanoparticles that could cross the blood-brain barrier [195]. Due to their peculiar solubility, Zabihi et al used hyperbranched PGL to prepare nanoparticles in aqueous solutions for the delivery of tacrolimus (TAC), a hydrophobic drug [196].…”
Section: Applicationsmentioning
confidence: 99%
“…It was found that despite being similar in size, drug release profile and in vitro cytotoxicity, the PLA-HBPG NPs showed significantly longer blood circulation and significantly less liver accumulation than PLA-PEG copolymers (Figure 12). Similarly, copolymers consisting of a PLA core and a HBPG shell modified with adenosine, were used to form nanoparticles that could cross the blood-brain barrier [195]. Due to their peculiar solubility, Zabihi et al used hyperbranched PGL to prepare nanoparticles in aqueous solutions for the delivery of tacrolimus (TAC), a hydrophobic drug [196].…”
Section: Applicationsmentioning
confidence: 99%
“…Ease of administration and the possibility of repeated dosage regimens are its main benefits. However, even with the best reported strategies to enhance transport across the BBB, intracranial accumulation of agents has been low, with about 1% of the injected dose reported to accumulate in the tumor in some cases [9,10]. Furthermore, systemic administration of nanocarriers inevitably results in abundant delivery to other tissues, such as the liver and lung, thereby increasing the risk of toxicity and undesired side effects.…”
Section: Nanomaterials For Local Drug Deliverymentioning
confidence: 99%
“…On the other hand, their use is limited by their low storage stability and encapsulation efficiency, together with a rapid leakage of hydrosoluble molecules. Polymeric NPs, properly modified to obtain an effective passive or active trans-BBB permeability, were also profoundly investigated for drug delivery to the CNS (Kreuter 2014 ;Saucier-Sawyer et al 2015 ;Vilella et al 2015 ). Among them, surfactant-coated nanoparticles, which represent the most investigated models (Steiniger et al 2004 ;Petri et al 2007 ;Wilson et al 2008 ;Sun et al 2015 ), are able to drive drugs across the BBB by exploiting the adsorption of low density lipoproteins (LDL) from blood plasma onto the nanoparticle surface and the interaction with the LDL receptors on the plasma membrane of the endothelial cells.…”
Section: Nanoparticles For Drug Deliverymentioning
confidence: 99%